Advances, challenges and future directions in web-based GIS, mapping services and applications: an introduction - Li, S.; Veenendaal, Bert; Dragicevic, S. (CRC Press, Taylor and Francis Group, 2011)
This introductory chapter presents an overview of recent advances in webbased Geographic Information Systems (GIS), mapping services and applications, and identifies some of the issues and challenges faced by researchers and professionals in the field. Primarily driven by current advances in web technologies and the expressed needs from geospatial communities, the field has evolved rapidly over the last two decades. The uncertainty of future technology developments makes it difficult to predict what the future holds. Nevertheless, we identify some trends and potential directions for web-based mapping and services.